2000
DOI: 10.1007/bf03166912
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ knowledge of perioperative care

Abstract: Patients' knowledge of perioperative care is limited, with very little change during hospital stay. Novel educational approaches may be required to increase basic medical knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
8
0
3
Order By: Relevance
“…Preoperatif anestezi bakısı, operasyon için hastayı değerlendirmeye ek olarak hastaya, anestezi uygulamaları ve anestezi doktorunun rolü hakkında bilgi vermesi açısından önemlidir (4). Hastalar sıklıkla genel, rejyonel anestezi ve operasyonla ilgili kaygılar taşır (7,8).…”
Section: Cinsiyetinizunclassified
See 1 more Smart Citation
“…Preoperatif anestezi bakısı, operasyon için hastayı değerlendirmeye ek olarak hastaya, anestezi uygulamaları ve anestezi doktorunun rolü hakkında bilgi vermesi açısından önemlidir (4). Hastalar sıklıkla genel, rejyonel anestezi ve operasyonla ilgili kaygılar taşır (7,8).…”
Section: Cinsiyetinizunclassified
“…Anestezi doktorları sıklıkla tanınmayan doktorlardır (3). Bu, operasyon planlanan hastaların kısa süre önce hastaneye çağırılması ve karmaşık bir ortama maruz kalmaları gerçeğine bağlanabilir (4). Hastaların birçoğu, çok fazla hastane personeli ile karşılaştıkları için operasyon öncesi anestezi doktoru ile karşılaştığını hatırlamaz (5).…”
Section: Introductionunclassified
“…In a study investigating patients' knowledge of common medical terms and their surgical care, findings revealed that many held misconceptions about pain management and a significant number were unaware that the anaesthetist was medically qualified (Laffey 2000). It is important to recognise how familiar we may be with our hospital world, but for many it remains a frightening mystery.…”
Section: Patient Barriersmentioning
confidence: 99%
“…Previous anaesthetic experience has not been found to improve patients' perception of anaesthesia (Kindler et al 2002). This perception was previously found to be poorer in males, older patients and patients in the lower socio-economic groups (Laffey et al 2000). The poor perception was also more pronounced when the role of the anaesthetist outside the theatre was assessed (Khan et al 1999).…”
Section: Introductionmentioning
confidence: 97%